On the tracks of an uninvited guest, the Asian tiger mosquito, Aedes albopictus in Cyprus - Piccinno, Riccardo; Fiorenza, Giulia; Vasquez Christodoulou, Marlen; Bouyer, Jeremy; Notarides, Gregoris; Gomulski, Ludvik Marcus; Meletiou, Soteris; Akiner, Mustafa M; Michaelakis, Antonios; Forneris, Federico; Maga, Giovanni; Gasperi, Giuliano; et al. (My University, 2025)
Aedes albopictus, the Asian tiger mosquito, which is listed among the world's 100 most dangerous invasive species, is the main vector of chikungunya, dengue and Zika viruses. This mosquito species has rapidly dispersed and invaded much of the globe assisted by its life history traits and high propagule pressure driven by human activities. Aedes albopictus is currently widespread across mainland Europe and the Mediterranean region, including the islands. Cyprus remained free of Ae. albopictus until October 2022, when specimens were recorded for the first time in Limassol district, including the port area. Understanding the processes associated with the introduction, expansion and establishment of this vector in Cyprus is of primary importance to mitigate its dispersal on the island, and to implement control methods to prevent disease outbreaks. A genetic analysis of these invasive specimens collected in Limassol district and in areas from the Central Mediterranean was performed to obtain a genetic portrait of the demographic history of the invasive mosquitoes on Cyprus.
Keywords: Aedes albopictus; Asian tiger mosquito; Cyprus; Invasive; Vector